2020
DOI: 10.1055/a-1167-1703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enhanced personal protective equipment on colonoscopy performance during the COVID-19 pandemic

Abstract: Background and study aims Using personal protective equipment (PPE) can reduce risk of disease transmission. During the COVID-19 pandemic, enhanced PPE (EPPE) is recommended when performing endoscopy. We aimed to evaluate the impact of EPPE on colonoscopy performance when compared to standard PPE (SPPE). Patients and methods A review of electronic medical records and endoscopy reports of consecutive patients who underwent colonoscopy during two similar one-month time periods (in 2019 and during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…There have been few studies on this subject but one similar one showed no difference in overall procedure time (including cecal intubation rate) between pre and post COVID-19 colonoscopy standards. 8 This was the opposite of our findings, however, this study had a lower power (N=256) compared to our study which may have skewed their results. Our study demonstrated that CIR was decreased from 2019 to 2020 (p=0.04).…”
Section: Discussioncontrasting
confidence: 96%
“…There have been few studies on this subject but one similar one showed no difference in overall procedure time (including cecal intubation rate) between pre and post COVID-19 colonoscopy standards. 8 This was the opposite of our findings, however, this study had a lower power (N=256) compared to our study which may have skewed their results. Our study demonstrated that CIR was decreased from 2019 to 2020 (p=0.04).…”
Section: Discussioncontrasting
confidence: 96%
“…On the other hand, wearing EPPE causes evident physical discomfort to the endoscopist and justifiable concern is present about the impact of EPPE on success rates and quality outcomes of endoscopic procedures. The impact of EPPE on upper gastrointestinal endoscopy and colonoscopy performance was investigated, but the effect of EPPE on ERCP quality outcomes was yet to be elucidated [10,11]. Our study showed that outcome measures such as cannulation success rate, cannulation time, difficult cannulation rate, unintended pancreatic duct cannulation rates, number of cannulation attempts, and length of hospital stay are not negatively affected by the use of EPPE compared to SPPE.…”
Section: Discussionmentioning
confidence: 76%
“…The novel coronavirus disease (COVID-19) has been declared a pandemic by the World Health Organization (WHO). 24,25 During the COVID-19 pandemic, the WHO issued an advisory to avoid crowded places. 26 The Japanese government also recommended avoiding the three C's: closed spaces, crowded places, and close contact settings.…”
Section: Discussionmentioning
confidence: 99%